Plant Symbiotic bacteria as the provider of Machines Fuel's hydrogen (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
Some of symbiotic bacteria as nitrogen-fixing in the roots of Leguminoz plants is producing H2 which in some of these bacteria, hydrogenase enzymes returns some of this produced hydrogen to the stabilization cycle to produce ATP, but some of these hup-Rhizobium have not mentioned enzyme and so produce H2 gas. Hydrogen gas as the renewable and important fuel in the industry is produced by several costly ways. This research tries to start some effort in order to producing of Hydrogen by natural symbiotic bacteria and its related laboratorial barriers.